2014
DOI: 10.1093/rheumatology/keu011
|View full text |Cite
|
Sign up to set email alerts
|

Primary cardiac disease in systemic lupus erythematosus patients: protective and risk factors--data from a multi-ethnic Latin American cohort

Abstract: Primary cardiac disease occurred in 14.1% of SLE patients of the Grupo Latino Americano de Estudio de Lupus cohort and pericarditis was its most frequent manifestation. African origin and lupus damage were found to be risk factors, while CNS involvement at or before recruitment and antimalarial treatment were protective. Primary cardiac disease had no impact on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
0
21
1
1
Order By: Relevance
“…20 We, however, could not find any prospective association of CNS involvement with pericarditis or pleurisy in any of our analysis.…”
Section: Epidemiology and Outcomescontrasting
confidence: 57%
See 1 more Smart Citation
“…20 We, however, could not find any prospective association of CNS involvement with pericarditis or pleurisy in any of our analysis.…”
Section: Epidemiology and Outcomescontrasting
confidence: 57%
“…The cross-sectional analysis includes all patients, and thus has Lupus Science & Medicine 20 reported that 'primary cardiac disease', including pericarditis (81.2% of all cases), was associated with African-Latin American ethnicity. Because serositis had been thought to be one pathogenic mechanism, it is quite surprising (and not understood) why pericarditis is associated with African-American ethnicity, whereas pleurisy is not.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,37 Anti-SSA/SSB antibodies have been found to be associated with cardiac involvement in cSLE 37,38 and anti-malarial therapy protects from future SLE-associated cardiac diseases. 39 …”
Section: Cardiac Manifestationsmentioning
confidence: 99%
“…37,39 The incidence of cSLE-associated pericarditis ranges from 10-38%. 37,[39][40][41] The clinical presentation, electrocardiogram (EKG) and echocardiographic (ECHO) findings of pericarditis due to cSLE are indistinguishable from those from other causes. Tachycardia, fever, substernal chest discomfort, positional chest pain, diminished heart sounds and rarely friction rub are the typical presenting symptoms.…”
Section: Pericarditismentioning
confidence: 99%
“…Cardiovascular diseases are frequent in SLE patients. There were regional and racial differences in cardiac manifestations and related risk factors in patients with SLE [6]. The pathological and clinical characteristics of SLE have not been completely elucidated until now.…”
Section: Introductionmentioning
confidence: 99%